2017
DOI: 10.1123/jpah.2016-0528
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions for Promoting Objectively Measured Physical Activity of Adults With Type 2 Diabetes: A Systematic Review

Abstract: Our systematic review of the literature indicated that a variety of interventions approaches were effective in increasing PA temporarily during the intervention period. Interventions that use objective methods in measuring PA and have long term improvement in overall PA are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Nevertheless, the overall positive results suggest that using wearable technology is also a promising tool to promote PA in healthcare settings. Similar to other reviews (14,16), large heterogeneity was found in the study characteristics. However, after excluding 2 studies based on leave-one-out sensitivity analyses, heterogeneity was acceptable.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Nevertheless, the overall positive results suggest that using wearable technology is also a promising tool to promote PA in healthcare settings. Similar to other reviews (14,16), large heterogeneity was found in the study characteristics. However, after excluding 2 studies based on leave-one-out sensitivity analyses, heterogeneity was acceptable.…”
Section: Discussionsupporting
confidence: 84%
“…Literature reviews have shown that interventions that include objective monitoring of PA are moderately effective in healthy subjects and relatively inactive populations (13)(14)(15)(16). However, the methodology of these studies differs considerably.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes care givers are encouraged to give advice on physical activity and such advice may be combined with using a pedometer or a comparable self-monitoring device (4, 5). Pedometers have shown positive effects on increased physical activity in short term in populations with type 2 diabetes (3,(6)(7)(8)(9) and are recommended for use to increase motivation to be physically active (10,11). Yet, it is unclear whether self-monitoring alone, or in combination with counseling is the most feasible and effective alternative (8,9,12).…”
Section: Introductionmentioning
confidence: 99%
“…Professional and regular counseling might be one strategy to start with. Such approaches, among others, include face-toface exercise or behavioral/cognitive consultation, or motivational phone calls promoting physical and leisure sports activities [2,13,14]. With professional support and repeated contacts, which seem to be important for behavioral changes [8], people might overcome initial inhibitions, start being active or increase their activity level and continue to be active on a regular basis as they experience the benefits of being so (e.g.…”
Section: Introductionmentioning
confidence: 99%